(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
The study aims highlight on Al-Jahiz with regard to the table narrations, which include around the table (Al-Khawan), and linking that relationship with the what is going on with miserliness that these interlocutors had and highlighting the role of dialogue trait of And and doing its types and functions to show the extent of integration between saying character and the attribute that it bears, specifically with between the words of the table narratives, the research vision was to dive into the descriptive regard to the lifestyle when analytical trend of the deep motives of misers, the way they talk, think and in the dialogue based on attending the table and its belongings, so we found a difference theorizing side, and The research included two aspects, a .the level of the interlocutors terminological definitions regarding we had a pause to explain the linguistic and the table-narrative text, and another applied dialogue, its types and functions within samples that we chose among the stories, anecdotes and analytical side to a group of emptiness of Al-Jahiz, which was specialized in the presence of the table anecdotes of the fertile ground in laying the main pillars of We have a what is related to it, to be and analytical and descriptive method in highlighting the dialogue research, relying on the reveals to us the extent of the miserliness It .exists between the characters image that interlocutor, after Al-Jahiz transmitted it to us in an endearing of the interviewee or the repulsive way. Our study tools were of non-traditional types and functions of and not so that dialogue that were the key to entering the world of miserliness and miserliness was based we would have the freedom to choose the samples on which the research ,and its dialogue structure that exists then within the framework of the table narratives actions and to arrive at a summary of the relationship between the characters in terms of It revolves between them that qualities with linking them to speech through the dialogue either by semantic persuasion or by intimidation and and is enticement